Wilayah Gerak Earth Hour Menjadi Sarana Pemerintah dan Swasta Meraih Dukungan Publik - Mardiana, Siva Yolla (ijd-demos, 2019)
the purpose of Earth Hour and the World Wide Fund for Nature (WWF) invite people around the world to continue to be a part of the social movement in the field of climate change with one of the energy-saving activities. In their campaign, Earth Hour proved to be a dominant force among other powers, associated with the three pillars of power, between political power and economic power. Environmental issues have become a global issue, a variety of damage that occurs on earth has become a serious concern by many. There are many organizations, communities and also mass movements that are concerned with environmental issues. Earth Hour is a global movement that initially campaigned energy savings with its peak event by turning off the electricity in 60 minutes at the end of March every year. Earth Hour movement spread over 153 countries around the world and 28 cities in Indonesia. The research was the focus in the area of motion Earth Hour; The Political environmental theory which was used in this research is Petersonâ€™s theory, those are the government, the private sector and social movement itself. This type of research is a qualitative study using a descriptive study. The researcher obtained data by conducting in personal experience and study literature. Data analysis techniques include data reduction, data display, and conclusion. The Conclusion of this study is in Earth Hour has its own characteristics to do such as lobbying to local authorities, then how to lobbying with other people who have the capability to influence public opinion, cooperate with other NGOs and raise social issues in the community to lobby with the private sector. In this area of movement Earth Hour is used as best as possible by the government and private sector to achieve their interests outside environmental-related policy issues.Tujuan Earth Hour dan World Wide Fund for Nature (WWF) mengundang orang di seluruh dunia untuk terus menjadi bagian dari gerakan sosial di bidang perubahan iklim dengan salah satu kegiatan penghematan energi. Dalam kampanye mereka, Earth Hour terbukti menjadi kekuatan dominan di antara kekuatankekuatan lain, yang terkait dengan tiga pilar kekuatan, antara kekuatan politik dan kekuatan ekonomi. Masalah lingkungan telah menjadi masalah global, berbagai kerusakan yang terjadi di bumi telah menjadi perhatian serius banyak orang. Ada banyak organisasi, komunitas dan juga gerakan massa yang peduli dengan masalah lingkungan. Earth Hour adalah gerakan global yang awalnya mengkampanyekan penyempurnaan energi dengan acara puncaknya dengan mematikan listrik dalam 60 menit pada akhir Maret setiap tahun. Gerakan Earth Hour tersebar di 153 negara di seluruh dunia dan 28 kota di Indonesia. Penelitian ini fokus di bidang gerak Earth Hour; Teori lingkungan politik yang digunakan dalam penelitian ini adalah teori Peterson, yaitu pemerintah, sektor swasta dan gerakan sosial itu sendiri. Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan penelitian deskriptif. Peneliti memperoleh data dengan melakukan pengalaman pribadi dan mempelajari literatur. Teknik analisis data meliputi reduksi data, tampilan data, dan penarikan kesimpulan. Kesimpulan dari penelitian ini adalah di Earth Hour memiliki karakteristik tersendiri untuk melakukan seperti melobi pihak berwenang setempat, kemudian bagaimana melobi dengan orang lain yang memiliki kemampuan untuk mempengaruhi opini publik, bekerja sama dengan LSM lain dan mengangkat masalah sosial di masyarakat untuk melobi dengan sektor swasta. Dalam bidang pergerakan ini Earth Hour digunakan sebaik mungkin oleh pemerintah dan sektor swasta untuk mencapai kepentingan mereka di luar masalah kebijakan terkait lingkunganÂ